FBR2 modulates ferroptosis via the SIRT3/p53 pathway to ameliorate pulmonary fibrosis - Cheng, Yu; Jiao, Yang; Wei, Wan; Kou, Mengjia; Cai, Yaodong; Li, Yang; Li, Hao; Liu, Tonghua (Frontiers in Pharmacology, 2025)
BackgroundIdiopathic Pulmonary Fibrosis (IPF), an interstitial lung disease of unknown etiology, remains incurable with current therapies, which fail to halt disease progression or restore lung function. However, Feibi Recipe No. 2 (FBR2), a clinically validated traditional Chinese medicine formula, exhibits potential as an IPF treatment.ObjectiveThis study aimed to investigate the regulatory effect of FBR2 on ferroptosis through the SIRT3/p53 pathway and its therapeutic potential in improving IPF.MethodsPulmonary fibrosis was induced in C57BL/6J mice by intratracheal instillation of Bleomycin (BLM), followed by FBR2 treatment via gavage. Assessments encompassed histopathology, ELISA for cytokine detection, IHC and Western blot for protein expression analysis, and qRT-PCR for gene expression quantification. Transmission electron microscopy (TEM) was used to observe mitochondrial morphology. The roles of Erastin and the SIRT3 inhibitor 3-TYP were also explored to elucidate FBR2’s mechanisms of action.ResultsFBR2 treatment significantly mitigated BLM-induced lung injury in mice, as evidenced by improved body weight and survival rates, and reduced levels of inflammatory cytokines, including IL-6 and TNF-α. FBR2 decreased collagen deposition in lung tissue, as shown by Masson’s staining and IHC detection of Col-I and α-SMA, confirming its anti-fibrotic effects. It also reduced iron and MDA levels in lung tissue, increased GSH-Px activity, improved mitochondrial morphology, and enhanced the expression of GPX4 and SLC7A11, indicating its ferroptosis-inhibitory capacity. Furthermore, FBR2 increased SIRT3 levels and suppressed p53 and its acetylated forms, promoting the translocation of p53 from the nucleus to the cytoplasm where it co-localized with SIRT3. The protective effects of FBR2 were reversed by Erastin, confirming the central role of ferroptosis in pulmonary fibrosis treatment. The use of 3-TYP further confirmed FBR2’s intervention in ferroptosis and cellular senescence through the SIRT3/p53 pathway.ConclusionFBR2 shows therapeutic potential in a BLM-induced pulmonary fibrosis mouse model, with its effects mediated through modulation of the ferroptosis pathway via the SIRT3/p53 mechanism. This study provides novel evidence for the targeted treatment of IPF and offers further insights into its pathogenesis.